A Compact Dual-Band Cross-Notched T-Shaped Antenna for High-Efficiency 2.4/5.8 GHz Wi-Fi Energy Harvesting in Self-Powered IoT Devices - Ansah, John Nyamekye (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2026)
This paper presents a dual-band cross-notched T-shaped monopole antenna developed for efficient ambient RF energy harvesting in the 2.4 GHz and 5.8 GHz Wi-Fi bands. The antenna occupies a compact size of 40 40 1.6 mm³, making it suitable for space-constrained IoT and biomedical devices. The proposed antenna demonstrates excellent impedance matching, achieving S11 values of -23.225 dB at 2.4 GHz and -29.096 dB at 5.8 GHz, with corresponding VSWR values of 1.1483 and 1.0727, respectively. It achieves wide impedance bandwidths of 0.71 GHz (2.07–2.78) GHz and 1.78 GHz (5.07–6.85) GHz, yielding fractional bandwidths of 29.28% and 29.87%, ensuring stable operation across both Wi-Fi bands. The antenna measures gains of 2.10 dBi and 4.29 dBi, with directivities of 2.52 dBi and 4.58 dBi, supported by high radiation efficiencies of 90.78% and 93.43% at the two resonant frequencies. The cross-notched T-shape configuration contributes significantly to achieving compactness and enhanced electromagnetic performance, while strategically positioned rectangular notches at the upper-left and lower-right corners are instrumental in achieving dual-band operation. The results demonstrate the antenna’s strong suitability for RF energy harvesting, where high efficiency and wide impedance bandwidth are essential for maximising RF captured power. In summary, the proposed antenna provides a balanced combination of compact size, high radiation efficiency and broad bandwidth, establishing it as a robust candidate for the next-generation battery-less IoT and low-power medical systems.